DEVELOPING WOPIPOPU (WORDLESS PICTURE POP-UP) BOOK MEDIA ON SCIENTIFIC LEARNING AT GRADE 4 ELEMENTARY SCHOOL - Syopiani Oktavia; Syachruroji; Nana Hendracipta (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop scientific-based Wopipopu Book media as a means of visual learning style for students at grade IV elementary school and to determine the feasibility of the Wopipopu Book media. This research was conducted at SD Negeri Kebon Jahe, Kecamatan Serang, Serang, involving 23 grade IV students in a limited trial. This research and development used a model modified by Sugiyono. This model consists of six stages, namely problem analysis, data collection, product design, design validation, design revision, and product trial. The instruments of this research were questionnaires for media validation by lecturers and questionnaires for students. Based on the results of data analysis, it was concluded that the quality of Wopipopu Book learning media was categorized as very feasible with a percentage of 92.8% from two material experts, feasible with a percentage of 75.8% from two linguists, and 91.5% from two media experts. Furthermore, the percentage of students’ responses to the Wopipopu Book in the trial was 84.64% in the excellent category.